The Human Side of Structural Transformation - Porzio, Tommaso; Rossi, Federico; Santangelo, Gabriella (American Economic Review, 2022)
We document that nearly half of the global decline in agricultural employment was driven by new cohorts entering the labor market. A new dataset of policy reforms supports an interpretation of these cohort effects as human capital. Using a model of frictional labor reallocation, we conclude that human capital growth led to a sharp decline in the agricultural labor supply, accounting, at fixed prices, for 40 percent of the decrease in agricultural employment. This aggregate effect is halved in general equilibrium and it reflects the role of human capital as both a mediating factor and an independent driver of labor reallocation. (JEL J22, J24, J43, L16, O13, O14, Q10)